Determination of the electronic parameters of nanostructure SnO2/p-Si diode - Caglar, Yasemin; Caglar, Mujdat; Ilican, Saliha; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2009)
The current-voltage and capacitance-voltage characteristics of the nanostructure SnO2/p-Si diode have been investigated. The optical band gap and microstructure properties of the SnO2 film were analyzed by optical absorption method and scanning electron microscopy, respectively. The optical band of the film was found to be 3.58 eV with a direct optical transition. The scanning electron microcopy results show that the SnO2 film has the nanostructure. The ideality factor, barrier height and series resistance values of the nanostructure SnO2/p-Si diode were found to be 2.1, 0.87 eV and 36.35 k Omega, respectively. The barrier height obtained from C-V measurement is higher than obtained from I-V measurement and this discrepancy can be explained by introducing a spatial distribution of barrier heights due to barrier height inhomogeneities, which are available at the nanostructure SnO2/P-Si interface. The interface state density of the diode was determined by conductance technique and was found to be 8.41 x 10(10) eV(-1) cm(-2). It is evaluated that the nanostructure of the SnO2 film has an important effect on the ideality factor, barrier height and interface state density parameters of SnO2/p-Si diode. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SnO2; Sol-gel spin coating; Heterojunction diode